A Literature Review of Modern Branding - Csák, Krisztián; Juhász, Csilla (International Journal of Engineering and Management Sciences, 2025)
In the modern business landscape, branding goes beyond identifying products and services; it has become a crucial factor for corporate success. The leadership branding, and employer branding emerges as a key strategic tool in gaining competitive advantage, fostering loyalty, and enhancing engagement. Personal branding, as the conscious presentation of individual values and capabilities, supports leaders in strengthening credibility and trust. Leadership branding encapsulates a leader’s personality and style, serving as an inspiring example within the organization. Moreover, employer branding reflects the corporate culture and workplace values, making the organization attractive to talented employees. The aim of the study is to demonstrate how personal branding, including leadership branding and employer branding, can contribute to the more successful operation of a company, highlighting the synergy between the different levels of branding and their economic and social impacts.